The Role of Green Human Resource Management and Job Satisfaction in Affecting Employee Performance During The Covid 19 Pandemic - Ruma, Zainal (PT Maju Malaqbi Makkarana, 2024)
The aim of this research is to determine the implementation of environmentally friendly human resource management in the employee environment of a commercial company, especially at PT. Taka Bonerate Mandiri. The aim of this research is to understand how management applies the GHRM concept and its impact on job satisfaction and hand performance, especially during the Covid-19 outbreak. The aim of this research is to determine the relationship between the variables studied, including dependent and independent variables, with using a quantitative style. The exploration sample was taken from PT Taka Bonerate Mandiri workers totaling 76 respondents. The slice system is carried out through a questionnaire distributed to the HR department of PT. Taka Bonerate Mandiri which consists of staff and operations. Analysis of respondents' answers shows that the variables of environmentally friendly HR operations and job satisfaction are interrelated and have an impact on employee performance in the business company PT. Taka Bonerate Mandiri.